STRATEGI KOMUNIKASI PEMERINTAH DESA DALAM MENGIMPLEMENTASIKAN APLIKASI SMART KAMPUNG SEBAGAI INOVASI PELAYANAN PUBLIK DIGITAL - Hagi Rohidatul Umam; Safrieta Jatu Permatasari; Herwin Kurniadi (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
This research discusses how the communication strategy implemented by the Grogol Village Government in running the Smart Village application program as a form of digital-based public service innovation. The background of this research departs from the importance of utilizing information technology to improve the quality of community services at the village level. This application is expected to simplify the administrative process, as well as provide faster and more efficient access to services for residents. However, its implementation in the field still faces various obstacles, such as the lack of public understanding of digital technology, limited supporting facilities, and a strong conventional service culture. This research was conducted using a descriptive qualitative approach and relied on data collection methods in the form of observation, in-depth interviews, and documentation. The results show that the communication strategy implemented by the village government reflects the five main elements of communication according to Harold Lasswell, namely: who conveys (communicator), what is conveyed (message), through what channel (media), to whom (message receiver), and what impact is caused (effect). Although various forms of socialization have been carried out, the effectiveness of communication has not fully reached all elements of society. Therefore, a more effective communication strategy is needed that actively involves the community, and is in line with social conditions and digital capabilities and digital capabilities of villagers. Increasing digital literacy and providing adequate infrastructure are important supporting factors for the success and sustainability of the Smart Kampung application so that it can be maximally utilized.